Domain recombination: a workhorse for evolutionary innovation - Apic, Gordana; Russell, Robert B. (Science signaling, 2010)
Although the combination of modular domains within proteins has been proposed as a determining feature of evolutionary innovation and flexibility, direct evidence for this mechanism of evolution has been sketchy. Two papers, one creating new domain combinations in the yeast mating pathway and another involving a comprehensive analysis of protein function and domain architecture across major organisms, have provided firm evidence that the recombining of domains can lead to evolutionary innovation. The results will guide future studies in synthetic and evolutionary biology.
Gesehen am 24.11.2022